(untitled) (African Journal of Biomedical Research, 2021)
Solanum nigrum is a vegetable plant belonging to the family of Solanaceae. The ability to ascertain the quality and quantity of the chemical composition of a plant provides an insight on the possible optimum exploitation of the plant for ethnomedicinal and pharmaceutical purposes. This study was carried out to determine the phytochemical constituent and proximate composition of Solanum nigrum leaf from Ojo area of Lagos, Nigeria. Phytochemical screening and Proximate composition of Solanum nigrum leaf was performed using standard procedures. From the study, qualitative analysis of the aqueous extract of Solanum nigrum showed that alkaloid, saponin, flavonoid, tannin, phenol, terpenoids, cardiac glycoside were present while anthraquinone and steroid were not detected. Quantitative phytochemical analysis showed the constituents to be in the following concentrations: phenol (38.17 ±0.33mg/100g), flavonoids (34.78 ± 0.26 mg/100g) and terpenoids (34. 92 ± 0.28 mg/100g), tannin (30.32 ± 0.24 mg/100g), cardiac glycoside (30.23 ± 0.22 mg/100g), saponin (18.06 ± 1.39 mg/100g) and alkaloid (12.61 ± 0.81 mg/100g). Proximate composition included carbohydrate (71.91± 0.43%), protein (2.21 ± 0.06%), crude fat (0.49 ± 0.10), moisture (1.65 ± 0.09%), ash (3.49 ± 0.17%) and crude fibre (20.23 ± 0.19%). Phytoconstituents of S. nigrum from Ojo area of Lagos State are comparable to those from other parts of the world. With the exception of steroids, phytoconstituents of S. nigrum from Ojo area of Lagos State are comparable to those from other parts of the world. The presence of these phyto-constituents suggests their medicinal value.